THE INFLUENCE OF NEGLECTFUL PARENTING STYLE TOWARD THE ATTACHMENT BUILT BETWEEN MOTHER AND DAUGHTER AS ADOLESCENT IN “GIRL IN PROGRESS” MOVIE BY PATRICIA RIGGEN - HIDAYATI, DEVIY (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords : parenting style, developmental psychology, attachmentHumans cannot livealone in this world. They also need a place to stay andform their personalities. The first place that forms their personality is home, aplace where they live, set affection, feeling, and aspiration. At home, they meetpeople who take roles in their development, and parents are the first that form it. The way the parents raise their children takes a big role in their childrendevelopment. Everything that they teach to their children will affect theirchildrens’ developments and lives. Related to the background of the study, thisstudy aims to answer two following questions. The first, what kinds of parentingstyles are used by Ansiedad’s parents? And the second, what are the effects of the parenting style to the attachment between Ansiedad and her parents?In this study, developmental psychology will be applied and only focusedon the adolescent developmental psychology. Then to analyze the data,theparenting style that is used by Ansiedad’s mother will be explained by the writer. The attachments as the result of parenting styles will also be explained.Based on the result of the study, the writer found that neglectful parentingstyle is used by Ansiedad’s parent. The effect of parenting style to the attachment between Ansiedad and her parents is insecure attachment. In this study, the writer found the kinds of insecure attachment, dismissing or avoidant attachment, resistant or ambivalent attachment, and unresolved or disorganized attachment.In conclusion, the way the parents raise their children is very important.Because, if the parents raised her children in a good way, it can make her children be a good children. On the other hand, if the parents raised her children with badly, it can make the children be bad children.This study is expected to be useful for English Department students. Moreover, the writer hopes the futureresearchers who are interested in developmental psychology, especially inparenting style, may use new complete references and different object of study.